Epidemiology of classic psychedelic substances: results from a Norwegian internet convenience sample - Kvam, Tor-Morten; Uthaug, Malin V.; Andersen, Kristoffer A. A.; Refsum, Birk Berggrav; Tunstad, Paula Aarseth; Stewart, Lowan Han; Jacobsen, Henrik Børsting; Grønnerød, Cato (Frontiers in Psychiatry, 2023)
The purpose of the article: In recent years, there has been a renewed interest in investigating the use of classic psychedelics such as psilocybin and lysergic acid diethylamide (LSD) in the treatment of mental disorders and substance use disorders. However, knowledge about the epidemiology of classic psychedelics in the Nordic countries is limited. Methods: We recruited adult, Norwegian participants who have had a memorable experience after taking a classic psychedelic substance. They filled in an anonymous internet survey with 119 items covering matters related to recreational use of psychedelics using a secure, web-based application. Data are presented by using descriptive statistics (frequencies, means, and standard deviations). Results: We recruited 841 participants, 770 (72% male; 88% 45 years or younger) of which were included in the data analysis. The intentions behind taking the psychedelic substance were mainly recreational (46.1%) or therapeutic (42.3%). Most participants reported that their most memorable experience was with psilocybin. As in modern era clinical trials, most participants were well-prepared before, did processing during, and did integration work after the experience, whereas only a minority were supported by a therapist. Self-perceived symptoms of various mental disorders and substance use disorders were prevalent in the sample. Most subjects reported improvements in their condition. Although adverse reactions were usually mild and short-lived, 4.2% lasted for one year or more. Persisting flashbacks were present for a year or more among 2.9% of the participants. Conclusions: In this cross-sectional sample of Norwegian, self-selecting adults, we shed light on what characterizes the most memorable experience with a classic psychedelic substance, including short- and long-term risks and benefits. For the most part, the psychedelic experience led to improvements in self-perceived symptoms of mental disorders and substance use disorders. However, a small subset experienced persisting adverse reactions.